2023
DOI: 10.3389/fmicb.2023.1208743
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis ER-08, a multifunctional plant growth-promoting rhizobacterium, promotes the growth of fenugreek (Trigonella foenum-graecum L.) plants under salt and drought stress

Margi Patel,
Shaikhul Islam,
Fohad Mabood Husain
et al.

Abstract: IntroductionSustainable agriculture and meeting the world's food needs face considerable obstacles from abiotic stresses such as soil salinity and drought. This critical issue was addressed by our current study, which sought to uncover multi-trait bioinoculants from hostile ecosystems that could help mitigate salinity and drought stresses at the same time.MethodsThe Bacillus subtilis ER-08 (BST) strain was isolated from the halotolerant plant Fagonia cretica which was collected from the Little Rann of Kachchh,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…Among them, the strains ATMLC92021 and ATMLC152021 were closely related to Bacillus subtilis . In previous studies, some strains of this species have been reported to improve the drought tolerance in sugarcane, fenugreek, and wheat [ 26 , 27 , 28 ]. In addition, the strain ATMLC102021 was closely related to B. tequilensis clade; this species was described as osmotic stress-tolerant and presented with the capacity to improve drought stress tolerance in maize, wheat, and eggplant [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the strains ATMLC92021 and ATMLC152021 were closely related to Bacillus subtilis . In previous studies, some strains of this species have been reported to improve the drought tolerance in sugarcane, fenugreek, and wheat [ 26 , 27 , 28 ]. In addition, the strain ATMLC102021 was closely related to B. tequilensis clade; this species was described as osmotic stress-tolerant and presented with the capacity to improve drought stress tolerance in maize, wheat, and eggplant [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The leaf area (cm 2 ) was measured by multiplying the leaf width (cm) by the leaf length (cm). Seed germination percentage was noted on 10 days after sowing (DAS), and percent (%) seed germination (Patel et al, 2023a ) was determined using the below mentioned formula:…”
Section: Methodsmentioning
confidence: 99%
“…The experimental pot soil was investigated twice (before and after JB treatment) for their physicochemical properties in accordance with the methods stated previously (Patel et al, 2023a). The standard serial dilution spread plate method was implemented to partially assess the dominant and viable pot soil microbiome where the microbiome population was quantified as colony forming unit per gram of soil (cfu g −1 soil) (Rao, 2005).…”
Section: Assessment Of Physicochemical and Microbial Characteristics ...mentioning
confidence: 99%
“…Postbiotics have specific defense mechanisms that effectively reduce the harmful effects of reactive oxygen species (ROS), which may degrade nucleic acids, lipids, carbohydrates, and proteins. Antioxidant enzymes, particularly superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), play important roles in combating reactive oxygen species ( Sahoo et al, 2019 ; Aghebati-Maleki et al, 2021 ; Patel et al, 2023 ; Sahoo and Chainy, 2023 ; Patani et al, 2023b ). Hydrogen peroxide (H 2 O 2 ) undergoes a catalytic transformation into molecular oxygen and water through the enzymatic action of CAT, which is ubiquitously found in various biological entities, including probiotics and other living organisms ( He Z. et al, 2019 ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%